Randomized pilot study of an individualized multimodal exercise, nutrition, and behavior intervention in breast cancer patients treated with ovarian function suppression: protocol proposal for The OvS Breast ENBI Project - Herrero López, Blanca; Castellanos Montealegre, Mónica; Soulas, Candelaria; Rufrancos, Begoña Arbulo; García-Ontiveros Cuéllar, María Luisa; del Monte Millán, María; Villarejo López, Lucía; López-Tarruella Cobo, Sara; Jerez Gilarranz, Yolanda; Echavarría Díaz-Guardamino, Isabel; Jara, Pablo; Jiménez, Miguel Martín; et al. (Frontiers in Oncology, 2025)
IntroductionBreast cancer (BC) is the most common malignancy among women in Spain and worldwide. Ovarian function suppression (OFS) is recommended as an adjuvant strategy for high-risk hormone receptor (HR)-positive premenopausal BC patients. However, OFS is associated with unfavorable changes in body composition, weight gain, and adverse cardiorespiratory and emotional effects. Multimodal, individualized interventions integrating nutrition, exercise, and psycho-oncological support have demonstrated safety and efficacy in promoting healthy body composition, weight control, and cardiorespiratory fitness (CRF). This study aims to evaluate the impact of a personalized multicomponent intervention in premenopausal BC patients receiving adjuvant OFS.Methods and analysisWe present the ENBI project study protocol proposal as a single-center, open-label, 2:1 randomized pilot study designed to assess the effects of a 12-week individualized program (nutrition, exercise, and psycho-oncological support) versus the World Health Organization (WHO) healthy lifestyle recommendations. Participants are premenopausal HR-positive BC patients undergoing adjuvant OFS. The study duration is estimated at 15 months. The primary endpoint is weight and body composition change, measured via scale and bioelectrical impedance analysis at baseline, post-intervention, and at 6- and 12-month follow-up. Secondary outcomes include CRF, cardiac variability, muscle strength, physical function, laboratory parameters, patient-reported outcomes (quality of life, fatigue, physical activity), systemic therapy-associated adverse events, and nutritional and psychological status. Exploratory outcomes include inflammatory markers (C-reactive protein, tumor necrosis factor alpha, adiponectin) and oncostatin-M. Due to the lack of prior data, the sample size was pragmatically set based on the Hospital General Universitario Gregorio Marañón (HGUGM) Tumor Board registry, with an estimated recruitment of 30 patients.Ethics and disseminationThe HGUGM Drug Research Ethics Committee (CEIm) has approved the study protocol. Results will be presented at national and international conferences and published in a peer-reviewed journal.Trial registration numberNCT06727487